Menakar Produk Regulasi Pemerintah Kabupaten/Kota yang Kondusif bagi Investasi di Daerah - FC Susila Adiyanta (Administrative Law Department, Faculty of Law, Universitas Diponegoro, 2018)
AbstractThe aim of regional autonomy and decentralization of the authority of the regency and city governments is to shorten the bureaucracy and optimize public services. In reality the products of regional regulations overlap their competencies, contradict the substance and material content with other regional regulations that are parallel, as well as the existing regulations above, which have implications for the emergence of the complexity of licensing bureaucracy, and uncertainty of society and business in carrying out activities business and investment activities, interests of capital owners, and business / trade, regional and national competitiveness. This study highlights the problems related to the relationship between the central and regional governments as determinants of regulations that are codified for investment, product characteristics of regency / city government regulations that are conducive to investment competitiveness in the region, and the competence of district / city governments in setting conducive regulations for investment using an empirical approach. The conclusion of the results of this study is that the synergy between the central and regional governments is needed in designing conducive regulations to encourage the business and investment climate in the region, namely the product of regional regulations that do not conflict with the higher applicable regulations, efficient in tariff setting taxes, regional levies, and do not result in a high cost economy, do not result in double taxation with central taxes or with other regional taxes / levies, are not discriminatory, guarantee legal certainty and are equal in the eyes of the law, there is standard certainty services related to licensing); and regulations that are environmentally friendly, namely local regulations that support the management of natural resources well so that natural resources can be utilized optimally and sustainably. Recommendations in this study are: Central and regional governments must synergize and harmonize regulatory products at the central and municipal district levels, the regency and city governments must take the initiative to revise regulations on taxes and levies whose substance and material content are contrary to the regulations above, district governments and the city in formulating and determining the direction of reform policy and the implementation of governance in the regions must be oriented and refer to hierarchical relations between the central government and regional governments to support national development.Keywords: District /City Government, Regulation, Investment Abstrak Tujuan otonomi daerah dan desentralisasi kewenangan pada pemerintah kabupaten dan kota diantaranya adalah memperpendek birokrasi dan mengoptimalkan pelayanan publik. Pada kenyataannya produk peraturan daerah yang tumpang tindih kompetensinya, bertentangan substansi dan materi muatannya dengan peraturan-peraturan daerah lainnya yang sejajar, maupun dengan peraturan-peraturan yang ada diatasnya, yang berimplikasi pada munculnya kerumitan birokrasi perijinan, dan ketidakpastian masyarakat dan dunia usaha dalam melakukan kegiatan usaha serta aktivitas investasi, minat pemilik modal, dan daya saing usaha/ perdagangan, perekomian daerah maupun nasional. Penelitian ini menyoroti permasalahan-permasalahan terkait dengan relasi antara pemerintah pusat dan daerah sebagai faktor penentu regulasi yang kodusif bagi investasi, karakteristik produk regulasi pemerintah kabupaten/kota yang kondusif bagi daya saing investasi di daerah, dan kompetensi pemerintah kabupaten/kota dalam menetapkan regulasi yang kondusif bagi investasi dengan menggunakan pendekatan empiris. Kesimpulan dari hasil penelitian ini adalah sinergi antara pemerintah pusat dan daerah diperlukan dalam merancang regulasi yang kondusif untuk mendorong iklim usaha dan investasi di daerah, yaitu diperlukan produk peraturan daerah yang sifatnya tidak bertentangan dengan peraturan-peraturan yang lebih tinggi yang berlaku, efisien dalam penetapan tarif pajak, retribusi daerah, dan tidak mengakibatkan ekonomi biaya tinggi, tidak mengakibatkan pungutan berganda (double taxation) dengan pajak-pajak Pusat atau dengan pajak/retribusi daerah lainnya, tidak diskriminatif, menjamin kepastian hukum dan kedudukan yang sama di mata hukum, adanya kepastian standar pelayanan yang berkaitan dengan perizinan); dan perda yang ramah terhadap lingkungan, yaitu perda yang mendukung pengelelolaan sumber daya alam dengan baik agar sumber daya alam dapat dimanfaatkan secara optimal dan berkelanjutan. Rekomendasi pada penelitian ini yaitu: Pemerintah pusat dan daerah harus bersinergi dan mensikoronkan produk regulasi di tingkat pusat dan daerah kabupaten kota, pemerintah daerah kabupaten dan kota harus berinisiatif merevisi regulasi pajak dan retribusi yang substansi dan materi muatannya bertentangan dengan peraturan yang ada diatasnya, pemerintah kabupaten dan kota dalam merumuskan dan menetapkan arah kebijakan reformasi dan penyelenggaraan pemerintahan di daerah harus berorientasi dan mengacu pada hubungan hierarkhi antara pemerintah pusat dan pemerintah daerah untuk mendukung pembangunan nasional. Kata Kunci: Pemerintah Kabupaten/Kota, Regulasi, Investasi